ENT 530 Social Media Portfolio: Frunchie / Khaleela Syauna Ahmad Nadzri - Ahmad Nadzri, Khaleela Syauna (2021)
Frunchie is a company which focusing on selling munching cookies. This type of food is very trending among Malaysians which can be considered as one of the best selling cookies. Generally, it is cookies/ crunch that been served with premium callebaut chocolate. Frunchie is one of pioneer company that improvised the cookie with exclusive ingredients such as edible rose petals. white premium callebaut chocolate, almond nibs, cookies and cream.